STRATEGI DAN MEDIA PEMBELAJARAN YANG KREATIF DAN INOVATIF PADA MATA PELAJARAN AKIDAH AKHLAK DI MADRASAH - Nurlaili; Qolbi Khoiri; Albetrik Meizontara; Hafidzah Nurhasanah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to analyze creative and innovative strategies and media in teaching Aqidah Akhlak in Madrasas. This research uses a type of library research. Research Results: Aqidah Akhlak learning strategies can be in the form of: 1) Direct Learning Strategies (direct instruction), 2) Indirect Learning Strategies (indirect instruction), 3) Interactive Learning Strategies (interactive instruction), 4) Learning Strategies through Experience (experiential learning ), 5) Independent Learning Strategy. Meanwhile, creative and innovative media takes the form of: 1) Print media, which can be in the form of textbooks, worksheets, or modules that can be used by teachers and students. 2) Audio media is implemented, for example at the MI level in phase B (Class 3) which can use audio in the form of sound speakers related to Asmaul Husna material, so that students can listen carefully and memorize it easily. 3) Visual Media can be applied in Phase D (Class VII) of MTS, such as the material